Is it more than employability?: Revisiting employers’ perception of graduates’ attributes - Santos, P. (2022)
Higher education is confronted with two broad missions, either prepare graduates for the world of work, or prepare well-rounded students that combine broad-spectrum qualities of citizenship, responsibility, and professional expertise. The employability skills have been widely studied, while the attributes related to holistic education are still scarcely investigated. This paper examines the skills and other attributes that employers seek when hiring graduates. It confronts the perceptions of employers regarding the skills associated with employability and the abilities and characteristics linked to holistic education. This is an exploratory research based on original and qualitative data collected in 2020 through interviews with employers (n=8) from different sectors in Portugal. Empirical findings indicate that all employers prioritise employability skills, such as communication, teamwork, and learning abilities. We found more dispersion regarding the attributes of holistic education and a large consensus was found for interdisciplinarity, self-reflection, and personal and social responsibility. The data show that the attributes that help to address society’s problems and challenges still seem to be regarded as quite irrelevant in the recruitment process.